2013
DOI: 10.1108/nfs-11-2011-0131
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bacterial and anti-fungal activity of coleus leaves consumed as breast-milk stimulant

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:215438 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The need for novel antimicrobials is vital to slow the global health emergency of antibiotic resistance [2][3][4][5][6] . Previous research of Coleus has shown antibacterial activity against gram-positive and gram-negative bacteria [13,14] . The demonstration of an additional novel activity of Coleus against S. agalactiae and S. pyogenes, provides further support for the development of Coleus as an antimicrobial of the future.…”
Section: Resultsmentioning
confidence: 99%
“…The need for novel antimicrobials is vital to slow the global health emergency of antibiotic resistance [2][3][4][5][6] . Previous research of Coleus has shown antibacterial activity against gram-positive and gram-negative bacteria [13,14] . The demonstration of an additional novel activity of Coleus against S. agalactiae and S. pyogenes, provides further support for the development of Coleus as an antimicrobial of the future.…”
Section: Resultsmentioning
confidence: 99%
“…10 Torbangun leaves are traditionally used to stimulate the production of breast milk from lactagogum as the local wisdom of the Batak people in North Sumatra. [11][12][13][14] Besides being used as lactagogum, Torbangun leaves are then used widely as antibacterial and antifungal, 15 blood pressure and cholesterol control. [16][17][18] Several studies have reported the ability of Torbangun leaves has been used in DM therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Since ancient times, its various species has been consumed as food for their nutritive values and their wide spectrum of traditional therapeutic activities. [8,9] These plants produce secondary metabolites with strong antioxidant, [10] anti-inflammatory, [10][11][12] antimicrobial, [13] antiviral, [14] and anticancer [12,15] properties.…”
Section: Introductionmentioning
confidence: 99%